Students’ Perception on the Information and Communication Technology (ICT) Tools in English Language Teaching - Anisa Husni Alkaromah; Endang Fauziati; Abdul Asib (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The pedagogies of English teaching are rapidly changing due to the advancement of information and communication technology (ICT). According to curriculum 2013, ICT is an essential component that should be integrated into each subject including English. It can be expected that it is essential for the teacher to use ICT in the teaching and learning process in order to help students to achieve a high quality of English subjects. To know the ICT role in the classroom so that this study was conducted to investigate senior high school students’ perceptions toward ICT usage in the EFL classroom. There are two students from the public school participated in Surakarta. This research design was a qualitative method with a case study approach to determine students’ perceptions and their experience in using ICT. Semi-structured interviews were used for data collection. The result indicated that the students perceived ICT usage and perceived access to ICT. Although the students use ICT and access it in the classroom, the domination of the level is at substitution and augmentation. These two levels are called enhancement. The findings reveal the usage of ICT in the EFL classroom. The students are reflected only to be able to use a basic function in a limited mobile application with only little change and improvement.